2021
DOI: 10.1038/s41467-020-20880-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic epidemiology of the early stages of the SARS-CoV-2 outbreak in Russia

Abstract: The ongoing pandemic of SARS-CoV-2 presents novel challenges and opportunities for the use of phylogenetics to understand and control its spread. Here, we analyze the emergence of SARS-CoV-2 in Russia in March and April 2020. Combining phylogeographic analysis with travel history data, we estimate that the sampled viral diversity has originated from at least 67 closely timed introductions into Russia, mostly in late February to early March. All but one of these introductions were not from China, suggesting tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 32 publications
3
70
0
Order By: Relevance
“…Since the beginning of the pandemic, the distribution of genetic lineages in the Russian Federation has notably changed [ 20 , 21 , 22 ]. In March 2020, the diversity was limited to a few genetic lineages, of which B.1 and B.1.1 were dominant (35.5% and 46.3% respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Since the beginning of the pandemic, the distribution of genetic lineages in the Russian Federation has notably changed [ 20 , 21 , 22 ]. In March 2020, the diversity was limited to a few genetic lineages, of which B.1 and B.1.1 were dominant (35.5% and 46.3% respectively).…”
Section: Resultsmentioning
confidence: 99%
“…Although the COVID-19 outbreak in Russia started later compared to many neighboring European countries, Russia is currently among the six countries with the highest number of confirmed COVID-19 cases, as of 9 May 2021 [22,23]. Limited data suggest that the seroprevalence of SARS-CoV-2 infection in Russia was approximately 9-10% in May-June 2020 [24], reaching 19.6-31.3% [25][26][27] by the end of the year.…”
Section: Introductionmentioning
confidence: 99%
“…1 b). A recent genomic study has shown that most of the sampled sequences from Russia in the early stage are nested within other European subclades, which indicates multiple introductions of the virus from Europe [ 9 ]. Our simulation indicated that if travel restrictions were implemented five days earlier, 64.1% of the cases could have been avoided as of 20 May 2020, as shown in Fig.…”
mentioning
confidence: 99%